2015
DOI: 10.1039/c4cy00661e
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylation of oleic acid over Pt catalysts supported on small-pore zeolites and hydrotalcite

Abstract: The catalytic decarboxylation and further conversions of oleic acid to paraffins, branched and aromatic hydrocarbons over Pt supported on small pore zeolites and hydrotalcite are demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 34 publications
1
55
0
Order By: Relevance
“…In our studies, zeolite 5A beads acted as acid 36,45 catalytic support, providing a large surface area, and playing an important role on the dispersion of Pt. Our group 32,34 and independent groups 46,47 have observed that acidic supports promote a better (higher) dispersion of the noble metal and therefore result in improved catalytic activity for decarboxylation and dehydroxygenation reactions. STEM revealed that a better Pt dispersion was achieved when Pt was deposited on zeolite 5A as compared to neutral carbon pellets.…”
Section: Acs Catalysismentioning
confidence: 97%
“…In our studies, zeolite 5A beads acted as acid 36,45 catalytic support, providing a large surface area, and playing an important role on the dispersion of Pt. Our group 32,34 and independent groups 46,47 have observed that acidic supports promote a better (higher) dispersion of the noble metal and therefore result in improved catalytic activity for decarboxylation and dehydroxygenation reactions. STEM revealed that a better Pt dispersion was achieved when Pt was deposited on zeolite 5A as compared to neutral carbon pellets.…”
Section: Acs Catalysismentioning
confidence: 97%
“…Fig. 33 The presence of H 2 promoted the hydrogenation of oleic acid to stearic acid which then undergoes facile decarboxylation. 41,42 The metal organic framework Cu 3 IJBTC) 2 (BTC = benzene-1,3,5tricarboxylate) is an appealing material to employ as catalyst for the decarboxylation of fatty acid molecules due to the presence of Lewis acid coordination sites (Cu) in its framework.…”
Section: Resultsmentioning
confidence: 99%
“…Reaction conditions were chosen based on our previous experience in the decarboxylation of fatty acids 32,33 to optimize the yield of hydrocarbons. The reactions were conducted in a 100 mL stainless steel, high pressure batch reactor (Parr model 4560).…”
Section: Reaction Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the higher cost of noble metals hinders their use as catalytic phase for industrial-scale processes. A preliminary conclusion can be: NAL7 yield is close to that shown by the granulated activated carbon catalyst [14], and shows a higher catalyst performance compared to 5 wt % Pt supported on small-pore zeolites [13]. Pt-SAPO-34 5 wt % Pt 2 g of catalyst, P = 20 bar, T = 355 • C, t = 2 h. n-C 17 66.…”
Section: Conversion Of Oleic Acid By Hydrodeoxygenationmentioning
confidence: 99%